Determining the effect of ocular chemical injuries on topical drug delivery. (1st January 2021) - Begum, Ghazala; Leigh, Thomas; Stanley, David; Logan, Ann; Blanch, Richard James
Abstract: Ocular chemical injuries (OCIs) commonly cause ocular damage and visual loss and treatment uses topical therapies to facilitate healing and limit complications. However, the impact of chemical injury on corneal barrier function and treatment penetration is unknown. Therefore, the aim of this study was to determine the effect of OCI on drug penetration and absorption. Porcine corneal explants were used to assess histological damage, electrical resistance, and the trans-corneal penetration/corneal adsorption of reference compounds (sodium fluorescein and rhodamine B) and dexamethasone. Corneal explants were injured with either 1 M sulfuric acid, or 1 M sodium hydroxide. Dexamethasone penetration was measured using high-performance liquid chromatography (HPLC) and that of fluorescein and rhodamine using fluorescence. Dexamethasone corneal adsorption was measured using enzyme-linked immunoabsorbant assay (ELISA). Both acid and alkaline injuries reduced trans-corneal electrical resistance. NaOH injury increased hydrophilic fluorescein penetration (NaOH 8.59 ± 1.50E–05 cm.min −1 vs. Hanks' Balanced Salt Solution (HBSS) 1.64 ± 1.01E–06 cm.min −1 ) with little impact on hydrophobic rhodamine B (1 M NaOH 6.55 ± 2.45E–04 cm.min −1 vs. HBSS 4.60 ± 0.972E–04 cm.min −1 ) and dexamethasone penetration (1 M NaOH 3.00 ± 0.853E–04 cm.min −1 vs. HBSS 2.69 ± 0.439E–04 cm.min −1 ). By contrast, H2 SO4 decreased trans-corneal penetration of hydrophilic fluorescein (H2 SO4 1.16 ± 14.2E–07 cm.min −1 ) and of hydrophobic dexamethasone (H2 SO4 1.88 ± 0.646E–04 cm.min −1 ) and rhodamine B (H2 SO4 4.60 ± 1.42E–05 cm.min −1 ). Acid and alkaline OCI differentially disrupted the corneal epithelial barrier function. Acid injury reduced penetration of hydrophobic dexamethasone and rhodamine B as well as hydrophilic fluorescein, which may translate clinically into reduced drug penetration after OCI, while alkaline injury increased fluorescein penetration, with minimal effect on dexamethasone and rhodamine B penetration.